2019
DOI: 10.3389/fmicb.2019.01486
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity and pH Drive Soil Bacterial Community Composition and Diversity Along a Lateritic Slope in the Avon River Critical Zone Observatory, Western Australia

Abstract: Soils are crucial in regulating ecosystem processes, such as nutrient cycling, and supporting plant growth. To a large extent, these functions are carried out by highly diverse and dynamic soil microbiomes that are in turn governed by numerous environmental factors including weathering profile and vegetation. In this study, we investigate geophysical and vegetation effects on the microbial communities of iron-rich lateritic soils in the highly weathered landscapes of Western Australia (WA). The study site was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 151 publications
(171 reference statements)
2
28
0
Order By: Relevance
“…In this study, the method of network analysis revealed an appropriate way to discover how environmental changes affected microbial communities. Previous studies have shown that when the external environment changed, such as variations in soil properties, the diversity of microbial communities changed, which may be correlated with disturbances in soil characteristics [51][52][53]. Additionally, soil factors, such as pH, moisture content, total carbon content, and organic matter, have been reported to have a greater impact on the soil bacterial community structure and diversity in the ecological restoration of mining areas.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the method of network analysis revealed an appropriate way to discover how environmental changes affected microbial communities. Previous studies have shown that when the external environment changed, such as variations in soil properties, the diversity of microbial communities changed, which may be correlated with disturbances in soil characteristics [51][52][53]. Additionally, soil factors, such as pH, moisture content, total carbon content, and organic matter, have been reported to have a greater impact on the soil bacterial community structure and diversity in the ecological restoration of mining areas.…”
Section: Discussionmentioning
confidence: 99%
“…The highest soil salinity (EC e = 37 dS m −1 ) and lowest prokaryote diversity were found at bulk soils from the H plot irrigated with EC w of 9 dS m −1 . Most soil halophilic bacteria are expected to belong to Firmicutes, Proteobacteria (Das et al 2019), and Actinobacteria (O'Brien et al 2019). In this study, based on 16S rRNA sequencing, Proteobacteria was the most abundant phylum of bacteria, and its relative abundance increased by nearly 20% on average at the highest irrigation water salinity (EC w = 9 dS m −1 ) in comparison with the control with EC w of 0.8 dS m −1 .…”
Section: Soil Salinity As a Driver Of Microbial Diversitymentioning
confidence: 69%
“…Many field and laboratory experiments have shown the effects of salinity on decreasing soil microbial biomass, respiration, and enzymatic activity and diversity, especially in desert ecosystems (Wasserstrom et al 2017;Zhang et al 2019). Nonetheless, the extent to which the soil salinity drives microbial community changes is dependent on the nature of each study and its sample set (O'Brien et al 2019). Based on our experimental design and reviewed literature (Lozupone and Knight 2007), we Fig.…”
Section: Soil Salinity As a Driver Of Microbial Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the method of network analysis revealed an appropriate way to discover how environmental changes affected microbial communities. Previous studies have shown that when the external environment changed, such as variations in soil properties, the diversity of microbial communities changed, which may be correlated with disturbances in soil characteristics [46][47][48]. Additionally, soil factors, such as pH, moisture content, total carbon content, and organic matter, reportedly have had a greater impact on soil bacterial community structure and diversity in the ecological restoration of mining areas.…”
Section: Discussionmentioning
confidence: 99%